2012
DOI: 10.17221/374/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Calcium regulates K<sup>+</sup>/Na<sup>+</sup> homeostasis in rice (Oryza sativa L.) under saline conditions

Abstract: To investigate the effects of Ca 2+ on cation accumulation and K + /Na + selectivity, in this study, two-week-old rice (Oryza sativa L.) plants were exposed to 25 or 125 mmol/L NaCl with or without 10 mmol/L CaCl 2 . At low salinity (25 mmol/L NaCl), Ca 2+ significantly decreased Na + accumulation in roots, increased K + accumulation in shoots, and maintained higher K + /Na + ratios in both roots and shoots of rice plants. At high salinity (125 mmol/L NaCl), however, Ca 2+ did not have any effects on Na + , K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…Decreased Mn was also observed under the salt-stress condition due to disrupted ion homeostasis. A similar salt-induced ion imbalance was reported in previous studies (Tuncturk et al 2008;Wu and Wang 2012). However, in our study, Mn supplementation decreased Na ?…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Decreased Mn was also observed under the salt-stress condition due to disrupted ion homeostasis. A similar salt-induced ion imbalance was reported in previous studies (Tuncturk et al 2008;Wu and Wang 2012). However, in our study, Mn supplementation decreased Na ?…”
Section: Discussionsupporting
confidence: 93%
“…efflux and triggers K ? leakage from plant cells (Cramer et al 1985;Shabala et al 2006;Wu and Wang 2012;Rahman et al 2016a). Higher Na ?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be associated with the enhancement of biological activity in the crop rhizosphere by some physiologically active substance in the OM. Wu and Wang (2012) reported that OM also decreased the sodium absorption ratio (SAR), indicating the migration of exchangeable Na + from the top soil layer and accumulation in lower depths with application of OM. The K + and Ca 2+ concentrations in leaf were maintained or increased under OM treatments (Table 3).…”
Section: Resultsmentioning
confidence: 99%